Transforming Pakistan : ways out of instability - Synnott, Hilary. (Adelphi (Series) (International Institute for Strategic Studies) ;, 2009)
Analyzes developments in Pakistan's volatile tribal regions, little understood in the West despite their profound implications for regional and international security, and examines the role of past events especially since 11 September 2001 in generating the animosity that many Pakistanis feel towards the West today.